2015
DOI: 10.4103/0259-1162.156373
|View full text |Cite
|
Sign up to set email alerts
|

Hypopituitarism: A rare sequel of cerebral malaria - Presenting as delayed awakening from general anesthesia

Abstract: We report a case of delayed emergence from anesthesia in a 37-year-old male who came for emergency laparoscopic appendicectomy. This patient is hailing from one of the endemic zones of Malaria, Orissa State in India. Two months ago he had cerebral malaria and was treated in our intensive care unit. After recovering from cerebral malaria, he presented to us for acute abdomen, and he was taken for emergency laparoscopic appendicectomy. He had delayed emergence of around 2 h to extubate from the time of completio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Authors also suggested that if hypoglycemia was present and/or if cortisol levels were within or below the normal range, stress dose steroids should be considered. Secondary adrenal insufficiency and central hypothyroidism leading to delayed anesthetic recovery have been reported in a patient with history of cerebral malaria [ 9 ]. Another interesting feature described in the literature includes cortisolemia leading to loss of immunity in pregnant women infected with falciparum malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Authors also suggested that if hypoglycemia was present and/or if cortisol levels were within or below the normal range, stress dose steroids should be considered. Secondary adrenal insufficiency and central hypothyroidism leading to delayed anesthetic recovery have been reported in a patient with history of cerebral malaria [ 9 ]. Another interesting feature described in the literature includes cortisolemia leading to loss of immunity in pregnant women infected with falciparum malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Many CM survivors suffer from long-term brain damage, as well as behavioural and mental health issues (common in children) [35]. Adults with hemiplegia, cerebral palsy, cortical blindness, deafness, cerebellar ataxia, and impaired cognition and learning are among the long-term consequences of CM [36].…”
Section: Clinical Features Of Cerebral Malariamentioning
confidence: 99%